Analisis Kebutuhan terhadap Aplikasi “Warkop-Peduli Covid” Pada Warkop Tarakan Brewing House - Haikal Haikal; Imaniar Sevtiyani (Pena Medika Jurnal Kesehatan, 2020)
Coffee shop has become a public space that provides freedom for visitors to engage in chatting, gathering and seeking information. The gathering activity that occurs can be a risk for Covid-19 transmission. The purpose to analyze the system that has been running and its weaknesses, to analyze the needs and the proposed system related to the application "Warkop Peduli Covid". This is a qualitative descriptive analysis with Evolutionary Web Development method which focuses on Context Analysis. In-depth interviews were conducted with the Coffee shop Tarakan Brewing House owner and Coffee shop visitors. The results are the needs of the owner of the Warkop Tarakan Brewing House, namely an application that immediately presents results related to the risk of transmission, updates on the latest information on the number of positive cases in Tarakan City which are officially released by the government and the presence of preventive information in the form of pictures or videos. Meanwhile, the needs of visitors to Coffee shop Tarakan Brewing House are to ensure that personal data can be kept confidential. In addition, the information presented must be readable or easy to understand. The proposed system to be developed is a Web-based “Warkop Peduli-Covid” to facilitate independent risk assessment of Covid-19 and information related to the prevention and current conditions of Covid-19. Keywords: Needs analysis, coffee shop, covid-19 personal risk assessment apps